Seasonal Energy Storage with Power-to-Methane Technology - Imre, Attila R. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
For a sustainable future, the need to use renewable sources to produce electricity is inevitable. Some of these sources-particularly the widely available solar power-are weather-dependent; therefore, utility-scale energy storage will be more and more important. These solar and wind power fluctuations range from minutes (passing cloud) to whole seasons (winter/summer differences). Short-term storage can be solved (at least theoretically) with batteries; however, seasonal storage-due to the amount of storable energy and the self-discharging of some storage methods-is still a challenge to be solved in the near future. We believe that biological Power-to-Methane technology-especially combined with biogas refinement-will be a significant player in the energy storage market within less than a decade. The technology produces high-purity methane, which can be considered-by using green energy and carbon dioxide of biological origin-as a Renewable Natural Gas, or RNG. The ease of storage and use of methane, as well as the effective carbon-freeness, can make it a competitor for batteries or hydrogen-based storage, especially for storage times exceeding several months.